The Implementation of Library Delivery Program in Untia Fisherman's Village - Darwis, Muh.; Musmin, Musmin; Jamaluddin, Jamaluddin; Arhas, Sitti Hardiyanti (Khizanah al-Hikmah : Jurnal Ilmu Perpustakaan, Informasi, dan Kearsipan, 2024)
This research addressed the gap in access to information and education, particularly in remote areas without permanent libraries. It examines the role of library delivery programs in enhancing literacy, providing equitable access to educational resources, and promoting lifelong learning in underserved communities. The study was conducted in Untia Village, a fishing community in Biringkanaya District, Makassar, Indonesia, with eleven informants. Data were collected through observation, interviews, and documentation. The findings highlighted the implementation of the Library Delivery Program in Untia Village, evaluated across three key indicators. First, the program’s alignment with the community’s needs, particularly the fishing population, which is distant from regional libraries. Second, the compatibility of the program with the implementing group, notably students who serve the community. Third, the alignment between the program's objectives and the needs of the target group. Despite these positive indicators, the study revealed that the program has not yet reached its full potential in terms of implementation. This research has implications for global efforts to bridge information access gaps in rural and underserved communities. Future research could explore the scalability of library delivery programs in diverse cultural and geographic contexts, with a focus on refining implementation strategies and measuring long-term impacts on literacy and education.